Bhutan : Technical Assistance Report-SARTTAC Report on National Accounts Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the findings and recommendations made the IMF mission to assist the Bhutanese authorities in improving estimates of annual GDP, and in developing methods for compiling quarterly GDP estimates. The mission found that the National Statistics Bureau (NSB) is engaged in a range of projects to improve Bhutan's national accounts statistics. Updated annual GDP statistics signal an improvement in data quality, which should enhance policymakers' ability to formulate and operationalize evidence-based decisions. Significant improvements to Bhutan's national accounts statistics can be achieved using a three-step process. The NSB should also keep in mind the need to incorporate methodological and conceptual/definitional revisions during the benchmarking and rebasing process.